The Rule of Owning and Raising Dogs between Permissibly and Prevention and the Consequences of the Companionship with them – A Comparative Juristic Study – - Saleh, Mohamed Atia (Journal of Islamic Sciences, 2020)
This research deals with the Sharia provisions related to Owning & breeding dogs in Islamic jurisprudence, and explaining the regulations of what is Prohibited and non-forbidden with evidence considered by the majority of jurists, and to clarify the a divinely- revealed law resulting from direct contact and dealing with dogs, such as the dogs' purity and uncleanness, besides the impact of touching dogs on the purity of the human being, and the effect of licking the utensil on the purity of water and the vessel. Also, this research aims to explain the sharia provision for the dog putting any of its parts other than saliva in water or pot with reference to the sayings of the scholars to clarify the wisdom of the tasbeeh (washing utensil 7 times) whether they are for worshipping or its purification? It also aims to clarify the legally considered approach in clearing what the dog has licked, with reference to the sayings considered in each issue and its evidence and the discussions on it. and clarifying the preponderance, and the reason for its weighting, with reference to aspects of the scientific miracle in the Sunnah of the Prophet in some matters relating to those provisions.
Keywords: Owning dogs; breeding; Impurity; Purity; licking; little puppy